THE IMPACT OF INTELECTUAL CAPITAL DAN INTERNAL CONTROL SYSTEMS ON THE QUALITY OF FINANCIAL REPORTING IN PUBLIC SECTOR ORGANIZATION: EAST LUWU REGENCY BKAD CASE STUDY - Fatmawaty Alwy; Rismawati; Imam Pribadi; Muhammad Aqsa; Duriani (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research aims to examine the impact of intellectual capital and internal control systems on the quality of financial reporting in public sector organizations, with a special focus on District BKAD. East Luwu. Using a quantitative research design, data was collected through secondary sources, including existing records and quarterly reports, and analyzed using SmartPLS. The analysis carried out consisted of validity and reliability tests, discriminant validity, inner model analysis, and direct influence analysis. The results show that intellectual capital and internal control systems have a weak but direct influence on the quality of financial reports, with path coefficients of 0.348 and 0.043, respectively, and P-Values exceeding 0.05, thus indicating an insignificant influence. These findings are in line with previous research, which underscores the role of intellectual capital in improving organizational performance and the importance of internal control systems for reliable financial reporting. The novelty of this research lies in its specific application to regional financial management bodies, which provides insight into the unique challenges and opportunities in improving the quality of financial reporting in BKAD East Luwu Regency. The study recommends continued investment in intellectual capital through targeted training programs and strengthening internal control systems to improve the quality and governance of financial reporting.